Vitamin D deficiency in the pathogenesis of leiomyoma and intravascular leiomyomatosis: A case report and review of the literature - Ian Judson; Christina Messiou (Elsevier, 2021)
This is a case of recurrent intravascular leiomyomatosis in a pre-menopausal woman of African-Caribbean heritage. She presented in 2006 with multiple uterine leiomyomata, tumour invading the inferior vena cava (IVC) extending into the right atrium, and pulmonary metastases. Her initial presentation was treated surgically. On recurrence she was treated by oestrogen suppression using a combination of goserelin and letrozole, with a substantial response. She subsequently reported further regression of disease following exposure to strong sunlight enabling her to discontinue oestrogen suppression without relapse. The hypothesis is that the benefit was due to vitamin D. The role of hypovitaminosis D in the pathogenesis of uterine leiomyomata is discussed, including epidemiology data demonstrating a link between ethnicity and risk and the proven mechanisms by which vitamin D controls oestrogen and progesterone receptor expression and influences other signalling pathways involved in the pathogenesis of leiomyomas. Data indicating the intermediate malignancy nature of intravascular leiomyomatosis, are discussed. We are not aware of other reports indicating a link between intravascular leiomyomatosis and a lack of vitamin D.